E-documentation and Crossborder Healthcare - Sjeničić, Marta (Medicine, Law & Society, 2015)
E-health is, in many European countries, one of the health care areas that are in the fastest development, due to the endeavor to apply modern information and communication technologies for the purpose of meeting the needs of citizens, patients, health professionals and the health policy creators. E-health potentials are virtually endless and can reach from the delivery of health information and health controle over the internet, through on-line consultations, issuing of drugs through electronic devices, till robotised surgeries or care of elderly population. European Union works actively in this field through different conventions and directives related to the patients’ rights in cross-border healthcare, but also protection of individuals with regard to the processing of personal data. One of the most recent and important documents in this field was Working Document 01/2012 on epSOS (Article 29 Data Protection Working Party), which was enacted January, 2012, and which was the basis for so-called epSOS project that has been impelemented from July 1, 2008 till June 31, 2014. The main objective of epSOS project is to shape, establish and evaluate the infrastructure of services which would enable the crossborder operability between the system of electronic health documentation in Europe. epSOS project aims to develop practical frame for e-health and information-communication infrastructure that would be basis for the safe access to the information on patients’ health, in the diferent European health systems.